Effect of secretion efficiency of mutant KRAS neoantigen by Lactococcus lactis on the immune response of a mucosal vaccine delivery vehicle targeting colorectal cancer - Alias, Nur Aqlili Riana; Hoo, Winfrey Pui Yee; Siak, Pui Yan; Othman, Siti Sarah; Mohammed Alitheen, Noorjahan Banu; In, Lionel Lian Aun; Abdul Rahim, Raha; Song, Adelene Ai-Lian (Multidisciplinary Digital Publishing Institute, 2023)
Colorectal cancer (CRC) is often caused by mutations in the KRAS oncogene, making KRAS neoantigens a promising vaccine candidate for immunotherapy. Secreting KRAS antigens using live Generally Recognized as Safe (GRAS) vaccine delivery hosts such as Lactococcus lactis is deemed to be an effective strategy in inducing specific desired responses. Recently, through the engineering of a novel signal peptide SPK1 from Pediococcus pentosaceus, an optimized secretion system was developed in the L. lactis NZ9000 host. In this study, the potential of the L. lactis NZ9000 as a vaccine delivery host for the production of two KRAS oncopeptides (mutant 68V-DT and wild-type KRAS) through the use of the signal peptide SPK1 and its mutated derivative (SPKM19) was investigated. The expression and secretion efficiency analyses of KRAS peptides from L. lactis were performed in vitro and in vivo in BALB/c mice. Contradictory to our previous study using the reporter staphylococcal nuclease (NUC), the yield of secreted KRAS antigens mediated by the target mutant signal peptide SPKM19 was significantly lower (by ~1.3-folds) compared to the wild-type SPK1. Consistently, a superior elevation of IgA response against KRAS aided by SPK1 rather than mutant SPKM19 was observed. Despite the lower specific IgA response for SPKM19, a positive IgA immune response from mice intestinal washes was successfully triggered following immunization. Size and secondary conformation of the mature proteins are suggested to be the contributing factors for these discrepancies. This study proves the potential of L. lactis NZ9000 as a host for oral vaccine delivery due to its ability to evoke the desired mucosal immune response in the gastrointestinal tract of mice.